Pyocyanin induces systemic oxidative stress, inflammation and behavioral changes in vivo. (24th July 2018) - Arora, Devinder; Hall, Susan; Anoopkumar-Dukie, Shailendra; Morrison, Rachel; McFarland, Amelia; Perkins, Anthony V.; Davey, Andrew K.; Grant, Gary D.
Abstract: Pyocyanin (PCN) is a virulence factor secreted by Pseudomonas aeruginosa ( P. aeruginosa ) that has been shown to have numerous toxic effects in both in vitro and in vivo studies. Such toxicities include pro-inflammatory and pro-oxidant mediated responses. It is hypothesized that PCN can cross biological membranes and reach the systemic circulation, but no previous studies have investigated this. The aim of this study was, therefore, to quantify PCN in plasma and assess if systemic responses were occurring after localized intranasal administration in C57BL/6 J mice. This was achieved through the plasma quantification of PCN and assessment of changes to behavior using two commonly used tests, the forced swimming test and the open field test. Furthermore, evidence of systemic oxidative stress and inflammation was measured using malondialdehyde (MDA) and TNF-α post PCN exposure. PCN was found to cross into systemic circulation but in a variable manner. Furthermore, significant increases in plasma TNF-α and MDA (both p  < 0.001) were observed along with changes in behavior indicative of systemic inflammatory responses.